Evaluation of Coffee Cherry Flour as a Functional Ingredient in Pastries - Alice-Jacqueline Reineke; Kristin Stadelmeyer; Catalina Acuña-Gutiérrez; Víctor M. Jiménez; Tania Chacón-Ordóñez; Oscar Acosta; Joachim Müller (Proceedings)
The coffee supply chain generates over 10 million tons of waste annually, with 70% comprising the fruit pulp and skin. This study investigates using coffee cherry flour from fresh coffee husk as an alternative ingredient in pastries with baking powder and baker’s yeast. We characterized the nutritional and physicochemical properties of this flour, developed high-fiber recipes, and evaluated the effects of substituting wheat flour with varying proportions of coffee cherry flour in plain cakes and sweet yeast breads. We found that coffee cherry flour reduced yeast dough volume increase and pastry specific volume in the coffee cherry flour pastries but enriched them with higher mineral and dietary fiber content compared to the wheat flour pastries.